Food diversity: its relation to children's health and consequent economic burden - Alfiah Hasanah; Bayu Kharisma; Sutyastie S. Remi; Asep Muhammad Adam; Adiatma Y.M. Siregar (BMC, 2024)
Abstract Background This study investigates the impact of low food diversity on the health status of children using the Dietary Diversity Score (DDS) and Dietary Serving Score (DSS) in a sub-district with the highest percentage of poor households. The economic burden of low food diversity was observed by analysing the cost of illness in the children with low food diversity. Methods Data from 329 children were collected. We determined the impact of DDS and DSS and other factors on the health status of children aged 2-14 years, using a probit model. The cost of illness (e.g., typhus, stomach ulcers, coughs, flu, and fever) due to low food diversity was calculated from medical registration fees, medical action costs, transportation costs, and other costs. Results The results shows that a 1% point increase in DDS or DSS potentially decreases children's health complaints by 10% and 8%, respectively. Given the current 26% prevalence of health complaints among children with low DDS, the annual economic burden reaches US$75.72 per child per household. In addition, the current 41% prevalence of children with low DDS resulted in an annual cost to the government of US$153.45 per child. Conclusions The effect of inadequate dietary diversity on children's health is potentially high and contributes to the economic burden on households and the government.